The Effect of Sanyinjiao Accupressure on Decreasing Dysmenorrhea Pain : Scoping Review - Navantri Muliyani; Endang Koni Suryaningsih (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Purpose: Dysmenorrhea, characterized by challenging menstrual flow or menstrual pain, affects approximately half of all girls and women. Various approaches exist to alleviate the intensity of dysmenorrhea pain, among which non-pharmacological therapy stands out. Sanyinjiao acupressure (SP6) represents a non-invasive, cost-free, and time-efficient method to address discomfort during dysmenorrhea. The purpose of this research to assess the impact of Sanyinjiao acupressure (SP6) in diminishing the intensity of dysmenorrhea pain, a review of prior research is warranted. Method: This research employed a scoping review methodology, drawing upon diverse references. The search for research literature was conducted across several databases, including PubMed, Science Direct, and EBSCO, using keywords such as "Sanyinjiao Acupressure" OR "SP6 Acupressure" AND "Dysmenorrhea," guided by the Arkshey & O'Malley Framework and the PRISMA-ScR Checklist. Utilizing the Joana Briggs Institute (JBI) Appraisal Tool, the study evaluated the quality of articles, culminating in the inclusion of 7 research journals spanning from 2010-2022, aligning with predefined inclusion and exclusion criteria. Results: Findings derived from the examination of seven eligible research journals indicate a substantial impact of Sanyinjiao acupressure (SP6) in mitigating the intensity of dysmenorrhea pain. Conclusion: Sanyinjiao acupressure (SP6) has been substantiated as an effective intervention in non-pharmacologically diminishing the intensity of dysmenorrhea pain.